Ekspansi Gerakan Islam Transnasional di Indonesia - Faizal Arifin (UIN Sunan Gunung Djati Bandung, 2021)
This book provides a kind of strategic recommendation or sharing of strategies and organized efforts, namely for Islamic organizations, institutions and communities in the form of 12 recommendation points to avoid infiltration and